Generation Z's Sustainopreneurship Readiness in Indonesian Tourism: Digital Innovation and Barriers - I Gede Gian Saputra; Dewa Ayu Nyoman Aridayanti; Dewa Ayu Made Lily Dianasari; Ida Bagus Putra Negarayana (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
This study investigates the sustainopreneurship readiness of Indonesia's Generation Z in the tourism sector, integrating the Theory of Planned Behavior, Self-Determination Theory, and the Triple Bottom Line framework. An explanatory mixed-method design was employed with 100 tourism students from two universities in Bali, Cronbach's a = 0.882. Descriptive statistics, chi-square tests, Spearman rank-order correlations, and thematic analysis were applied to quantitative and open-ended data. Results reveal that 84% of respondents expressed entrepreneurial interest (M = 4.30, SD = 0.76), with no statistically significant demographic variation across gender [x2(1) = 0.784, p = .376], age [X2(1) = 0.041, p = .840], or education level [X2(1) = 2.607, p = .106]. Digital technology and sustainability emerged as deeply integrated orientations (rs = .528, p < .001). However, capital access constraints (72%), regulatory barriers (57%), and managerial inexperience (65%) create a significant intention-behavior gap. This study advances the sustainopreneurship literature by distinguishing high dispositional readiness from insufficient structural ecosystem readiness among Generation Z in Indonesia.